1994
DOI: 10.1111/j.1539-6924.1994.tb00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Chlorination By‐Products from Hot Water Uses

Abstract: Exposures to chlorination by-products (CBP) within public water supplies are multiroute in water. Cold water is primarily used for ingestion while a mixture of cold water and hot water is used for showering, bathing others, dish washing, etc. These latter two activities result in inhalation and dermal exposure. Heating water was observed to change the concentration of various CBP. An increase in the trihalomethanes (THM) concentrations and a decrease in the haloacetonitriles and halopropanones concentration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 7 publications
2
29
1
Order By: Relevance
“…Storage of cold, tap water-based beverages and heating tap water to produce hot beverages reduce the concentrations of the volatile DBPs such as the trihalomethanes (Weisel et al, 1999 ). In addition, failure to account for dermal and inhalation exposures to DBPs is likely to lead to an underestimate of total exposure (Weisel and Chen, 1994;Backer et al, 2000 ). In this study, the use of private wells was not a source of misclassification since almost all tap water consumed at home and at work was from municipal supplies.…”
Section: Discussionmentioning
confidence: 84%
“…Storage of cold, tap water-based beverages and heating tap water to produce hot beverages reduce the concentrations of the volatile DBPs such as the trihalomethanes (Weisel et al, 1999 ). In addition, failure to account for dermal and inhalation exposures to DBPs is likely to lead to an underestimate of total exposure (Weisel and Chen, 1994;Backer et al, 2000 ). In this study, the use of private wells was not a source of misclassification since almost all tap water consumed at home and at work was from municipal supplies.…”
Section: Discussionmentioning
confidence: 84%
“…Weisel and Chen (1994) reported that calculated THM exposure levels were 50% higher when using THM concentrations in heated water than when using THM concentrations in cold water. In our study, THM concentrations were higher in bath or shower water than in cold tap water ( see Table 1) , and blood THM levels in people who showered or bathed were significantly higher than the blood levels of those who drank water.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these methods may not account for all relevant exposure routes. For example, household water use ( e.g., showering, bathing, flushing toilets, or using the dishwasher, washing machine, or faucets) can result in significant indoor air concentrations of volatile organic compounds ( VOCs ), including DBPs and other contaminants ( e.g., trichloroethylene ) ( Andelman, 1985;Giardino et al, 1992;Weisel and Chen, 1994;Wallace, 1997;Howard -Reed et al, 1999 ), and subsequent VOC exposure through inhalation will vary for different individuals within a household (Wilkes et al, 1996 ) . In addition, DBPs, such as chloroform, can be absorbed through the skin ( Jo et al, 1990a ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, however, estimates of exposure and risk have assumed that the concentration of THMs in hot water is equivalent to that in cold water and that no reactions of the residual chlorine with organic matter occurs once the water enters the home. Heating of water accelerates the formation of a number of chlorination by -products if a chlorine residual is present ( Weisel and Chen, 1994 ). A doubling of THMs was observed in water heated to 658C for 8 h, which is the period typical of what might occur in a household water heater before a morning shower ( obviously excluding electric power showers which heat water as and when required ).…”
Section: Effect Of Temperature On Uptakementioning
confidence: 95%
“…This would increase the inhalation and dermal exposure and risk associated with showering, by 50% above what would be calculated using the concentration in cold water. In contrast, concentrations of HANs and halopropanones, were found to have decreased to nondetectable levels in the water following heating for 8 h ( Weisel and Chen, 1994 ).…”
Section: Effect Of Temperature On Uptakementioning
confidence: 96%